ANALISIS PERHITUNGAN KETEBALAN PERISAI RADIASI PERANGKAT RIA IP10. - Benar Bukit; Kristiyanti Kristiyanti; Hari Nurcahyadi (BATAN, 2011)
CALCULATION ANALYSIS OF THE THICKNESS OF RADIATION SHIELD FORTHE RIA EQUIPMENT IP10. Calculation Anal ysis has been performed on the thickness of radiation shield for the design of the Radioi mmunoassay (RIA) IP10 counters using five detectors arranged in parall el . The calculati on is intended to ensure that the radiati on on each detector does not i nfluence each other. The radiation shield i s made of lead. The cal culation of lead thickness was based on the principle of the l ead plates absorptive power toward the gamma ray of a certain energy, whi ch is the function of l inear absorption coefficient and the material thickness. Assuming the use of Iodium-125(I-125) source with an activity 10 µCi, and expecting an absorptive power of 95%, calculations showed that the required lead thickness is equal to 0,013 cm. Since lead is soft and its avail ability in the market i s limited, lead plate of 2 mm thickness are used instead, so that counti ng result for the detectors do not infl uenceeach other. ANALISIS PERHITUNGAN KETEBALAN PERISAI RADIASI PERANGKAT RIA IP10. Telah dilakukan analisis perhitungan ketebalan perisai radiasi pada perancangan perangkat pencacah Radi oi mmunoassay (RIA) IP10 menggunakan 5 buah detektor yang disusun secara berjajar. Perhitungan dimaksudkan agar paparan radiasi yang diterima masing-masi ng detektor ti dak saling mempengaruhi. Perisai radiasi terbuat dari pelat ti mbal (Pb). Perhi tungan tebal pelat timbal berdasarkan prinsip Daya Serap (DS) radiasi pelat Pb terhadap pancaran sinar  pada energi tertentu, merupakan fungsi dari koefi sien linier dan tebal dari bahan. Hasil perhitungan dengan asumsi sumber radioisotop yang digunakan Iodium-125 (I-125) dengan akti vi tas 10 µCi dan DS yang diharapkan 95% didapatkan tebal Pb sama dengan 0,013 cm. Dengan mengingat sifat pel at Pb yang lunak dan ketersediaan ketebalan di pasaran terbatas, maka digunakan pelat Pb tebal 2 mm, sehingga pengukuran cacahan tidak saling mempengaruhi.